An altitude and distance correction to the source fluence distribution of TGFs. Issue 10 (30th October 2014) - Nisi, R. S.; Østgaard, N.; Gjesteland, T.; Collier, A. B.
Abstract The source fluence distribution of terrestrial gamma ray flashes (TGFs) has been extensively discussed in recent years, but few have considered how the TGF fluence distribution at the source, as estimated from satellite measurements, depends on the distance from satellite foot point and assumed production altitude. As the absorption of the TGF photons increases significantly with lower source altitude and larger distance between the source and the observing satellite, these might be important factors. We have addressed the issue by using the tropopause pressure distribution as an approximation of the TGF production altitude distribution and World Wide Lightning Location Network spheric measurements to determine the distance. The study is made possible by the increased number of Ramaty High Energy Solar Spectroscopic Imager (RHESSI) TGFs found in the second catalog of the RHESSI data. One find is that the TGF/lightning ratio for the tropics probably has an annual variability due to an annual variability in the Dobson‐Brewer circulation. The main result is an indication that the altitude distribution and distance should be considered when investigating the source fluence distribution of TGFs, as this leads to a softening of the inferred distribution of source brightness.